Acylation of Electron-Poor Alkenyl Sulfoxides: Diverse Transformations for the Synthesis of Polysubstituted Phenols and Functionalized Carbocycles - Li, Xiaoyu; Zhang, Qianyun; Xie, Yuanyuan; Zhou, Hongwei (Synthesis, 2023)
A protocol with available starting materials and mild conditions was developed for the synthesis of polysubstituted phenols and functionalized carbocycles via acylation of electron-poor alkenyl sulfoxides. The plausible mechanism was investigated.
Keywords: alkenyl sulfoxides; sulfonium ions; functionalized carbocycles; polysubstituted phenols; aromatization